LANGUAGE STYLE USED IN BLACKPINK’S SONG LYRICS “THE ALBUM” RECORDS 2020 - Miftakhul Jannah; Sudirman Sudirman; Aulia Hanifah Qomar (PHILOLOGY Journal of English Language and Literature, 2022)
Language style is a choice of words that have more meaning and the way to show about expression in many ways. This research focus on the using language style in Blackpink’s song lyrics “The Album” records 2020. The objectives of this research were to describe type and to find out the dominant type of language style in Blackpink’s song lyrics “The Album” records 2020. The writer uses descriptive qualitative design, in which the data are sentences that contain of language style in the lyrics. In analyzing the data the researcher applied qualitative descriptive.The result of this study, the researcher found 33 types of Rhetorical and Figurative Language Style which consist of 9 hyperbole, 1 litoses, 1 paradox, 10 simile, 8 metaphor, 2 metonymy, 2 allegory. Three types of language style simile, hyperbole, and metaphor are dominant.